Navigating celiac disease with small bowel capsule endoscopy: current state and future horizons - Matilde Topa; Mattia Corradi; Luca Elli; Yasmine Raji; Emanuele Lettieri; Nicoletta Nandi; Lucia Scaramella (Therapeutic Advances in Gastrointestinal Endoscopy)
Celiac disease (CeD) is a widely diffused chronic autoimmune disorder triggered by the ingestion of gluten, in genetically predisposed individuals. Small bowel capsule endoscopy (SBCE) plays a pivotal role as a noninvasive tool for diagnosing and monitoring CeD. This review aims to summarize the current and potential future role of SBCE in the field of CeD. SBCE offers the advantage of visualizing the entire small bowel, allowing the extent of disease involvement to be described. According to international guidelines, SBCE has a defined role in cases of inconclusive histopathology or when clinical suspicion persists despite negative duodenal biopsies. To date, more and more interest is shown toward its role in monitoring CeD, specifically in terms of mucosal healing, early detection of complications such as ulcerative jejunitis, or performing differential diagnosis among other small bowel diseases that mimic CeD. With the rise of artificial intelligence systems being applied in this field, the future role of SBCE in CeD is expected to improve diagnostic accuracy and streamline the evaluation process, allowing its use as a routine tool for monitoring and early diagnosis of CeD-related complications. The environmental impact of SBCE is still under debate, but increasing evidence is suggesting ways to apply circular economy to the capsule lifecycle, turning it into a more sustainable device. In conclusion, SBCE is increasingly recognized as a critical tool in the diagnosis and monitoring of CeD.